KISAH PENCIPTAAN KEJADIAN 1:1-2:4.2:5-25 SEBAGAI TEKS PENYATAAN IDENTITAS ISRAEL DAN SUMBANGANNYA BAGI PERSOALAN EKOLOGI - Mathias Jebaru Adon; Yulianus Hironi Ndua (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2022)
This study focuses on the analysis of the text of Genesis 1:1-2:4.2:4b-25 as a text to reveal the identity of Israel as God's chosen nation. This study aims to emphasize that the story of creation in the book of Genesis is not a chronological text of the creation of man and the universe but the story of Israel's faith journey as God's chosen nation. This research is motivated by the fact that the text of Genesis 1:1-2:4.2:4b-25 is often used as a basis for arbitrary human domination over the created world. Therefore, by knowing the history of the formation of the text, all forms of destruction of nature in the name of religion can be overcome. This research is a critical analysis of the text of Genesis 1:1-2:4.2:4b-25 as a narrative of Israel's journey of faith. This study found that the text of Genesis 1:1-2:4.2:4b-25 was written when Israel was experiencing an identity crisis due to the oppression and influence of other nations. Therefore, this research raises awareness that humans are not the center of creation but creatures who are given the responsibility to care for and preserve the universe.